Small intestinal diverticulum with bleeding: Case report and literature review. Issue 9 (March 2018) - Zhao, Lifang; Lu, Wei; Sun, Yinping; Liang, Junrong; Feng, Shanshan; Shi, Yongquan; Wu, Qiong; Wang, Jianhong; Wu, Kaichun
Abstract: Rationale: Small intestinal diverticulum with bleeding is an important reason for obscure gastrointestinal bleeding (OGB), in addition to tumor and vascular diseases. Small intestinal diverticulum with bleeding is difficult to detect by barium meal and angiographic methods and has been regarded as an important cause of obscure gastrointestinal tract bleeding in adolescents. Because of its complicated etiology and non-specific clinical manifestations, it is relatively difficult to detect small intestinal diverticulum with bleeding, especially in patients with a large amount of bleeding and hemodynamic instability. Patient concerns: This retrospective study collects clinical statistics of 19 patients admitted to our hospital from January 2010 to December 2016. Patients who had small intestinal diverticulum patients with bleeding were included in this study. Patients who were taking anticoagulants were excluded Diagnoses: Small intestinal diverticulum patients with bleeding. Interventions: This retrospective study describes the clinical features of patients with small intestinal diverticulum whose main symptom was gastrointestinal bleeding and analyze the literature on this topic, with particular reference to the clinical characteristics, pathological features, and choice of examination methods. Lessons: Small intestinal diverticulum with bleeding is a common cause of obscure gastrointestinal bleeding, but it is difficult to detect using normal examination methods. For patients with repeated gastrointestinal bleeding and no positive results found on gastroscopy and colonoscopy, endoscopy of the small intestine and CTE with contrast can be considered as a diagnostic modality.